Energy-using Durables – Why Consumers Refrain From Economically Optimal Choices - Schubert, Renate; Stadelmann, Marcel (Frontiers in Energy Research, 2015)
Sustainable development requires increasing the energy efficiency, decreasing the growth rates of energy demand, and decreasing the CO2 emissions. In many countries, households’ energy consumption is responsible for a considerable share of total energy demand and CO2 emissions. Energy-using durables are essential in this context. Aiming at sustainability, private households should buy more energy-efficient durables and use them in a more efficient way. In principle, it might even be economically optimal to buy the more energy-efficient products, since they result in lower total costs over their lifetime – thus resulting in a positive net present value (NPV). However, when observing private households’ purchase decisions, they often do not correspond to the economic optimum, resulting in an “energy-efficiency gap.” This paper investigates into the reasons for the persistence of such a gap between energy-efficient products that would be economically optimal – but from which consumers refrain – and less energy-efficient products that consumers actually own or buy although they entail larger life-cycle costs. Factors, which seem to deter private households from purchasing energy-efficient products with positive NPVs, are, for example, insufficient information, limited attention, or inertia. We will show how these and other factors hinder private households from identifying and realizing their economically optimal choices and how such barriers can be overcome. We will present how properly designed energy labels could help to overcome the information-related causes of inefficiently low energy-efficiency investments and provide some additional policy recommendations that could help reaching the aforementioned goal of a reduction of households’ energy demand and CO2 emissions in an adequate way.